Changes in Taste, and Migrations During the Anglo-French Blockade of Buenos Aires (1830-1850); [Cambios del Gusto y de Las Migraciones Durante el Bloqueo Anglofrancés en Buenos Aires (1830-1850)] - Lacoste, P (Arturo Prat University, 2024)
At the outset of the Cold War, the Chilean magazine ‘Se’ examines the early shift in wine tastes in the Río de la Plata region, following a shift from the Spanish-Creole paradigm to the French paradigm in the 1840s. The study focuses on the role of early French migration, half a century prior to the period of mass migration, and is based on both French and British sources, including commercial, diplomatic and political reports, with particular reference to debates in the French Parliament. It finds that the 15,000 French immigrants who settled in the Río de la Plata (River Plate) region between 1835 and 1850, made certain French products fashionable, particularly wine, thus contributing to the process of changing people’s tastes and consumption patterns. This phenomenon also had an impact on the subsequent development of the regional wine industry, with the gradual incorporation of the French model and the abandonment of the Spanish-Creole legacy, all within a context of growing Eurocentrism. © 2024, Arturo Prat University. All rights reserved.